The Oxford Handbook of the History of Nationalism. - Breuilly, John.
1 online resource (818 pages)
Keywords: Thirty-six essays by a team of leading scholars providing a global coverage of the history of nationalism in its different aspects - its ideas, its sentiments, and its politics.